Pelatihan Pengenalan Kosa Kata Bahasa Inggris untuk Anak-anak Dengan Metode Total Physical Response (TPR) - Susanti, Susi; Fauziah, Desna; Novendri, Trio; Dari, Wulan (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
The presence of an independent curriculum initiated by the Indonesian Minister of Education has begun to support the optimization of English language learning in elementary schools (SD). However, teaching English to elementary school children is a challenging matter. Teachers are expected to be able to have particular strategies that make it easier for children to enjoy English. Total Physical Response (TPS) is a technique for learning English that is innovative and fun for children. TPS uses body movements to interpret words and facilitate children to recognize English vocabulary. This training aims to help elementary school children to learn English vocabulary and create a pleasant classroom atmosphere. This community service activity was conducted at SDN 05 Sumanik Salimpaung district Tanah Datar Regency, West Sumatra, on Wednesday, 6 September 2023, from 08.00 until Finish. Thirty-three students were participated in this activity, including students from grades 4 and 5. This activity was successfully conductedl, and the participants participated enthusiastically in the whole program. According to results of oral quiz on the use of TPS method, students could comprehend and master the English vocabulary that was introduced quickly and very well.